Modeling and analysis of unsteady second-grade nanofluid flow subject to mixed convection and thermal radiation - Abbas, S. Z.; Waqas, M.; Thaljaoui, A.; Zubair, M.; Riahi, A.; Chu, Y. M.; Khan, W. A. (Soft computing (Berlin, Germany), 2022)
This article addresses the flow over an unsteady slendering stretching sheet considering second-grade nanofluid with mixed convection. By taking the features of non-linear thermal radiation, thermophoresis and Brownian diffusion effects are scrutinized. The flow is induced by a non-linear stretching surface of variable thickness. Essential features of combined zero mass flux and convective conditions are analyzed. The use of appropriate transformations results in the non-linear ODEs. Computations for the convergent series solutions are provided. Graphical illustrations assign the interpretations to quantities of physical interest. Nusselt number and skin friction are analyzed as well. By observing these results, it is evident that the attributes of nanoparticles and non-linear thermal radiation increase the temperature distribution.